¿Cómo influye la tasa de cambio y sus determinantes sobre las decisiones de política comercial? (2020)
The development of foreign trade in the Latin American region has been represented by periods of acceleration and stagnation, the result in some cases of political models and ideologies characterized by protectionism. It was until the end of the 20th century, and with the development of policies more inclined to the free market, that the processes of commercial opening reappeared with more force in the discourse of the governments of this region. However, integration into international trade has not progressed continuously or sufficiently, compared to what seemed to be imposed as the agenda in that period. This document seeks to explore the reasons why this process has had heterogeneous progress among countries and has been relatively slow in most of them. For this, a provocative hypothesis proposed by Villar and Esguerra (2005) for the case of Colombia is explored. This establishes an endogeneity of commercial policy with respect to variations in the exchange rate and the factors that generate them. In this paper we extend the scope of this analysis to a group of economies representative of the Latin American region, in addition to extending the period of analysis to capture not only the evolution of the 20th century but also the first years of the 21st century. The results obtained show that in the period between 2007 and 2019, the hypothesis proposed by Villar and Esguerra does not continue to be fulfilled for the Colombian case, otherwise with Argentina and Peru.